Is There Life Outside the ERM? An Evaluation of the Effects of Sterling's Devaluation on the UK Economy. - Hallett, A; Wren-Lewis, S (1997)
This paper makes a quantitative assessment of the impact of sterling s exit from the exchange rate mechanism (ERM) in September 1992, taking as given other events and other countries' policies as they happened. To do this we use two different econometric models, each with its own information set. One is a UK model using current (to 1995) information; the other a multicountry model with information as known in early 1992. We therefore examine the question with the benefit of hindsight and as the policy makers could have seen it at the time. The results are the same. Sterling's exit produced a period of recovery, real growth and little extra inflationary pressure. Excess capacity and competition in the labour markets may have led to lower inflation pressures. However, it was lower interest rates which proved growth creating in the UK, rather than sterling's devaluation, which proved growth diverting.